Outcomes of bleb excision and conjunctival advancement for leaking or hypotonous eyes after glaucoma filtering surgery - Tannenbaum, D P (Copyright 2004 British Journal of Ophthalmology, 2004)
Aim: To determine outcomes of bleb excision and conjunctival advancement for leaking or hypotonous eyes after glaucoma filtering surgery. Methods: In a retrospective case series the medical records of all patients who underwent bleb excision and conjunctival advancement surgery for bleb leaks or hypotony (defined as IOP less than 6 mm Hg, associated with reduced vision) at the Jules Stein Eye Institute and the Yale University Eye Center between January 1993 and June 2002 were reviewed. Only patients with more than 6 months of follow up were included. Complete success was defined as resolution of the pre-existing leak or hypotony, with maintenance of IOP ⩾6 and ⩽21 mm Hg, in the absence of further glaucoma surgery and without any glaucoma medication. Qualified success met the above criteria with or without the use of glaucoma medications. Success rates were analysed with Kaplan-Meier survival curves. Results: 49 eyes were included in the study; 13 eyes had overt bleb leaks, 27 eyes had hypotony. Nineteen patients underwent resuturing of sclera and/or placement of a pericardial graft in addition to bleb excision and conjunctival advancement. Mean preoperative IOP increased from 3.2 (SD 2.4) mm Hg (range 0–10 mm Hg) to 13.8 (4.8) mm Hg (range 6–29 mm Hg) at last follow up (p<0.0001). Mean preoperative visual acuity improved from 0.6 (0.3) logMAR (range 0–2) to 0.3 (0.3) logMAR (range 0–2) at final follow up (p<0.0001). 16 eyes (40%) were classified as complete success and 17 additional eyes achieved qualified success, for a total of 33 eyes (83%) achieving at least qualified success. There was no significant difference in the rate of complete success (p = 0.95) or qualified success (p = 0.88) between the group of patients who underwent bleb excision and conjunctival advancement alone versus those who also had resuturing of sclera and/or placement of a pericardial graft. Failures included three eyes that had persistent hypotony without leak, requiring additional bleb revision, and four with uncontrolled IOP, two of whom underwent additional glaucoma surgery. Conclusion: Bleb excision with conjunctival advancement is a successful procedure for bleb repair. This technique provides successful resolution of leaks and hypotony, maintains glaucoma control with or without medication, and preserves vision with minimal postoperative complications in a majority of eyes.